Conceptual and Logical Model Hire Purchase Management System for Boon Motor Enterprise (K) Sdn Bhd - Ang, Moon Thiak (2009)
This project is regarding the designing of conceptual and logical model of Hire Purchase Management System for Hire Purchase Company. The System will use client server system to run daily operations and able to smooth up the daily operation and reduce the operation cost as well. Prior to the development of the system, a study has been done so that the organization can gain real benefits from adopting a suitable Hire Purchase System. So, a Conceptual Model of the system has been made to simulate the model to determine the effectiveness of the system. The prototype will be developed know as Boon Motor Hire Purchase Management System (BMHPM). BMHPM able to control on the daily Hire Purchase transaction and also management system.